2018
DOI: 10.1177/0021998318771464
|View full text |Cite
|
Sign up to set email alerts
|

Effects of missing fasteners on the mechanical behavior of double-lap, multi-row composite bolted joints

Abstract: This paper presents a numerical investigation into the effects of missing fasteners on the mechanical characteristics of double-lap, multi-row composite bolted joints. A highly efficient explicit finite element model, which was validated effective and accurate by experiments, was developed and employed to conduct the virtual tests. Single-column and multi-column joints with various positions of missing fastener were considered. It is shown that the removal of fasteners can reduce the joint stiffness significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Atsushi Noma and Jianmei He [16] analyzed the spring characteristic effects of the spiral cutting bolt structure and the anti-loosening performance of threaded fasteners but lacked a detailed discussion and analysis on the bolt pre-tightening force characteristics. Fujian Zhuang and Puhui Chen [17] studied the effect of missing bolts on the mechanical properties of double-lapped multi-row composite bolt connections by numerical simulation but disregarded the bolt pre-tightening force and vibration characteristics. Yong-xiang Zhang et al [18] analyzed the vibration transmission characteristics of bolt connection structures based on ANSYS software and found that the inherent frequency of the system increased with the pre-tightening force.…”
Section: State Of the Artmentioning
confidence: 99%
“…Atsushi Noma and Jianmei He [16] analyzed the spring characteristic effects of the spiral cutting bolt structure and the anti-loosening performance of threaded fasteners but lacked a detailed discussion and analysis on the bolt pre-tightening force characteristics. Fujian Zhuang and Puhui Chen [17] studied the effect of missing bolts on the mechanical properties of double-lapped multi-row composite bolt connections by numerical simulation but disregarded the bolt pre-tightening force and vibration characteristics. Yong-xiang Zhang et al [18] analyzed the vibration transmission characteristics of bolt connection structures based on ANSYS software and found that the inherent frequency of the system increased with the pre-tightening force.…”
Section: State Of the Artmentioning
confidence: 99%